Optimization of the bioequivalence study of esomeprazole capsule contents after in vitro suspension in soft foods using HPLC - Alauddin, M; Hossain, KMZ; Rahman, MA; Kabir, ASMH; Khan, IH (Daffodil International University Journal of Science and Technology, 2010)
A bioequivalence study for the selection of the alternative and feasible mode of administration of esomeprazole pellets suspended in some common soft liquid foods has been done. 20 mg of four different brands esomeprazole pellets suspended in yogurt, orange juice, apple juice and milk were analyzed in the gastric environment using dissolution tester and high performance liquid chromatography. The release of the esomeprazole active was found more the 90% using these liquid foods except milk. The optimal release of the active was found in the system of apple juice (97.06%). Administration of the esomeprazole pellets suspending in apple juice may be a practical alternative for patients who cannot swallow an intact capsule. Keywords: Bioequivalence, Esomeprazole pellets, Soft foods, Gastric environment, Dissolution. DOI: 10.3329/diujst.v4i2.4368 Daffodil International University Journal of Science and Technology Vol.4(2) 2009 pp.59-61